The Blindspots Between Us - Tsipursky, Gleb (New Harbinger Publications, 2020)
When what you think you know gets in the way?this eye-opening guide offers a clear path to forging stronger, healthier, and more meaningful relationships. We all want positive, productive, and genuine relationships?whether it's with our family, friends, peers, coworkers, or romantic partners. And yet, time and time again, we all seem to make the same thinking errors that threaten or sabotage these relationships. These errors are called cognitive bias, and they happen when our brain attempts to simplify information by making assumptions. Grounded in evidence-based cognitive behavioral therapy (CBT), The Blindspots Between Us reveals the most common "hidden" cognitive biases that blind us to the truth, and which lead to the misunderstandings that damage our relationships. With this guide, you'll learn key skills to help you de bias?to stop, pause, and objectively observe situations before jumping to conclusions about others' motives. You'll also learn to consider other people's points of view and past experiences before rushing to judgment and potentially undermining your relationships. Being a human is hard. None of us are perfect, and we all have our blindspots that can get in the way of building the relationships we really and truly want, deep down. This much-needed book will help you identify your own blindspots, and move beyond them for better relationships?and a better world.